1997
DOI: 10.1111/j.1365-2133.1997.tb01122.x
|View full text |Cite
|
Sign up to set email alerts
|

Necrotizing granulomatosis of the breast

Abstract: We describe a case of necrotizing granulomatosis of Wegener's type involving the breasts of a 40-year-old man. There were no signs of generalized disease. Involvement of the breast is rare in Wegener's granulomatosis (WG). To date, 17 cases have been reported, and all were women. They predominantly presented with a unilateral breast mass, and mammary malignancy was the principal concern. In the majority of cases, breast lesions of WG have been a presenting sign of, or preceded, disseminated disease. Our patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…It may develop as an isolated manifestation, although the breast mass usually accompanies or precedes disseminated disease [3-7, 9, 12]. Seven patients with both breast and lung involvement have been reported in the literature [5,7], and granulomatous nodules of the breast with lung involvement were present in our case. The patient had been complaining of her symptoms for approximately a month, and sought medical attention at the very beginning of her disease.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…It may develop as an isolated manifestation, although the breast mass usually accompanies or precedes disseminated disease [3-7, 9, 12]. Seven patients with both breast and lung involvement have been reported in the literature [5,7], and granulomatous nodules of the breast with lung involvement were present in our case. The patient had been complaining of her symptoms for approximately a month, and sought medical attention at the very beginning of her disease.…”
Section: Discussionmentioning
confidence: 58%
“…Lesions have usually been detected on examination, in the form of palpable single or multiple nodules, with or without fixation of the overlying skin [8,25]. Other reports mention nodular lesions and multifocal skin ulcerations [5], tender breast mass with fever, retraction of the nipple, thickening of the skin [26,27], and clear discharge from the nipple [8]. Physical examination of our patient found a few palpable movable lesions, without skin or nipple abnormalities, in the left breast only.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mammary involvement in GPA patients is rare: patients (mostly women) present with a uni-or bi-lateral breast mass, which is either painful or not and, more rarely, skin inflammation/ulcerations or nipple discharge. One case of breast involvement in a man was reported (40 years old, bilateral breast masses and skin ulcerations, small-vessel vasculitis and granuloma) [83].…”
Section: Gpamentioning
confidence: 99%
“…In most of the cases, systemic GPA symptoms preceded the onset of breast symptoms [84][85][86][87]. Our literature review found 9 cases of GPA revealed by breast disease, initially restricted to the breast [82,83,[88][89][90][91][92][93][94]. In these cases, systemic symptoms occurred several weeks (3-24 weeks) after diagnosis of breast disease, and sometimes later (about 10 years) [90,91].…”
Section: Gpamentioning
confidence: 99%